2014
DOI: 10.3892/or.2014.3672
|View full text |Cite
|
Sign up to set email alerts
|

Ampelopsin reduces the migration and invasion of ovarian cancer cells via inhibition of epithelial-to-mesenchymal transition

Abstract: Ampelopsin has displayed anticancer activity in several types of cancers. However, no evidence has been reported for the direct effect of ampelopsin on ovarian cancer cell migration and invasion, and the underling mechanisms have not yet been clearly established. The aim of the present study was to investigate the influence of ampelopsin on the migration and invasion of ovarian cancer. Proliferation and viability of the ovarian cancer cells were detected by MTT assay. Migration and invasion of the cells were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…External stimuli can separate these factors from IkB, transfer them to the nucleus, and allow them to interact with their target genes to promote cancer cell motility and invasion. Inhibition of the EMT and NF-kB/Snail signaling pathway has been shown to significantly suppress metastasis in multiple cancer cell types, such as gastric adenocarcinoma cells SGC-7901 (Zhu et al, 2015) and breast cancer cells A2780 (Liu et al, 2015a). Moreover, suppression of the NF-kB activity and EMT-related proteins, such as vimentin, Snail, and Slug, has been shown to suppress metastasis in osteosarcoma cell lines MG-63, Saos-2, and U-2OS (Chang et al, 2015), indicating that cancer metastasis can be effectively suppressed by inhibiting the EMT and NF-kB/Snail signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…External stimuli can separate these factors from IkB, transfer them to the nucleus, and allow them to interact with their target genes to promote cancer cell motility and invasion. Inhibition of the EMT and NF-kB/Snail signaling pathway has been shown to significantly suppress metastasis in multiple cancer cell types, such as gastric adenocarcinoma cells SGC-7901 (Zhu et al, 2015) and breast cancer cells A2780 (Liu et al, 2015a). Moreover, suppression of the NF-kB activity and EMT-related proteins, such as vimentin, Snail, and Slug, has been shown to suppress metastasis in osteosarcoma cell lines MG-63, Saos-2, and U-2OS (Chang et al, 2015), indicating that cancer metastasis can be effectively suppressed by inhibiting the EMT and NF-kB/Snail signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A pipette tip was used to make straight scratches of the same width in the monolayer of U2OS cells on the surface of each well. U2OS cells were treated as follows: Control, physiological saline; TNF-α, 100 ng/ml for 24 h; TNF-α + ampelopsin, 50 µM ampelopsin for 2 h prior to TNF-α (100 ng/ml) incubation for 24 h; ampelopsin, 50 µM treatment for 2 h prior to physiological saline of equal volume for 24 h. Images were captured to measure the wound healing under the Olympus IX71 microscope (Olympus Corporation, Tokyo, Japan) (10).…”
Section: Western Blot Analysismentioning
confidence: 99%
“…Following re-suspension in the upper chamber, U2OS cells were treated as described above for the control, TNF-α, TNF-α + ampelopsin and ampelopsin groups. The cells remaining on the upper surface were gently wiped away with a cotton swab and the cells on the lower surface were fixed with 95% ethanol for 30 min and stained with 0.1% hexamethylpararosaniline following methanol fixation (Sigma-Aldrich) at 37˚C for 30 min (10). The number of cells on the lower surface of the membranes was quantified using the Olympus IX71 microscope.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, considerable research on the biological activity of DMY in China and abroad showed that DMY has many functions, such as antioxidant, antibacterial, anti-inflammatory, tumor inhibition, liver protection, and blood glucose and lipid regulation [3][4][5][6][7]. Studies also showed that as a new green additive in livestock production, DMY can be used to promote livestock growth, increase production performance, enhance animal immune systems, and improve meat quality [8].…”
Section: Introductionmentioning
confidence: 99%